Custom-made Gold Implant for Management of Lagophthalmos: A Case Report - Tuna, Suleyman Hakan; Gumus, Hasan Onder; Hersek, Nur (European Journal of Dentistry, 2008)
Lagophthalmos is defined as the inability to close the eyelids completely. This situation may lead to corneal problems such as epithelial defects, stromal thinning, exposure keratitis, bacterial infection, perforation, and blindness. A patient with lagophthalmos underwent insertion of a custommade gold weight implant. After implantation, the patient was able to close her eye and expressed high cosmetic and aesthetic results. Fabrication of gold weight implant by the means of a rolling machine is an effective and easy way and should be considered in the management of lagophthalmos. (Eur J Dent 2008;2:294-298)
Keywords: Lagophtalmos; Orbicularis oculi muscle; Eyelid; Gold weight implant